Implementation of a Digitalized Work System in the Administration Process for ADF and Stock Minus Submission Using the AppSheet Application : (Case Study at PT. Aspirasi Hidup Indonesia Tbk, Pluit Branch) - Pangestu, Aji Pujiyono (Jurnal Indonesia Sosial Sains, 2024)
Administration in a company is essential. Every day, the administration department is bustling, submitting damaged goods and negative stock. However, there are shortcomings in the administrative process, which still uses a manual method, namely using a logbook, so that the queue to submit damaged goods and the completion of stock minus becomes long and inefficient. The purpose of this study is to provide solutions to the administrative process problems. One way to increase the speed of the administrative process is to implement a digitalization system that employees can use. The data collection method used in this study is by conducting observations and interviews with employees. The implementation of this study is to make two app-sheet-based prototypes that cover the needs in submitting ADF for damaged goods and minus stock so that, from the results of this implementation, the administrative process runs quickly and efficiently.